Variabilidade genética de duas populações de Kinosternon scorpioides No Maranhão, Nordeste do Brasil, com base na região controladora do mtDNA. - NUNES, Mayara Monteles de Almeida (2016)
Kinosternon scorpioides, known as swear is one of the best known species of freshwater turtles in Brazil with wide distribution in South America in Central America and Mexico. In the state of Maranhão were found 06 species of freshwater turtles. Among the Terrapins, the swear is one of the least known to science. Knowledge of the genetic makeup of some sort is necessary to evaluate the variability levels found in natural populations and defining population structure by philogeography. Thus, the aim of this study was to evaluate the genetic diversity of populations had sworn the coastal region of Curupu-MA Island (L1) and the Continental Region of Baixada Maranhense in São Bento (L2). For genetic variability analysis was used to control region of DNA mitocondrial.O blood of the animals was collected and extracted DNA. The fragments of the mtDNA control region (CR) were PCR amplified, purified and sequenced. Fifteen specimens were analyzed between these six L1 region and L2 region nine. Individuals of L1 region is not newly introduced specimens according to analyze the haplotype network have generated with genetic distance L2 of individuals. The analysis of a control region of mtDNA may be relevant to species because it was found a clade forming a haplotype different from the other two species of the genus. In these analyzes it can be concluded that populations have genetic variability, noting the difference between these in the haplotype network generated and the differences with the external groups of aligned sequences, yet the deepening of genetic studies is likely to support strategies for the conservation of the species.